New records and distribution expansions of aquatic heteropterous from colombia (hemiptera, heteroptera) (2013)
Thirty three species water bugs were registered; 21 semiaquatic and 12 aquatic (Gerromorpha and Nepomorpha). Expansions of the geographical range for 24 species and nine species were recorded for the first time for Colombia Cryptocricos rufus DeCarlo, 1940; Gelastocoris bolivianus De Carlo, 1954; Ranatra tuberculifrons Montandon, 1907; Neoplea borelii, Kirkaldy, 1899; Hydrometra exalla Drake y Lauck, 1959; Hebrus plaumanni Porter, 1952; Merragata hebroides White, 1877; Rheumatobates drakei, Hungerford, 1954; Microvelia hinei Drake, 1920; for each of these species were considered a diagnosis and illustration of taxonomic characters. The distribution by department and municipality and an illustrative map was given for all species.  Nuevos registros y ampliación de la distribución de heterópteros acuáticos en Colombia (Hemiptera, Heteroptera) RESUMENSe registran 33 especies de chinches acuáticas; 21 semiacuáticas y 12 acuáticas (Gerromorpha y Nepomorpha). Se amplia el rango geográfico para 24 especies y nueve especies son registradas por primera vez para Colombia: Cryptocricos rufus DeCarlo, 1940; Gelastocoris bolivianus De Carlo, 1954; Ranatra tuberculifrons Montandon, 1907; Neoplea borelii (Kirkaldy, 1899); Hydrometra exalla Drake y Lauck, 1959; Hebrus plaumanni Porter, 1952; Merragata hebroides White, 1877; Rheumatobates drakei (Hungerford, 1954); Microvelia hinei Drake, 1920; para cada una de estas especies se considera una diagnosis e ilustración de los caracteres taxonómicos. Para todas las especies se proporcionan la distribución por departamento y municipio y un mapa ilustrativo.